Investments and Identities across Contexts: A Case Study of a Hong Kong Undergraduate Student's L2 Learning Experiences. Issue 3 (4th May 2019) - Sung, Chit Cheung Matthew
ABSTRACT: This article reports on a case study of a Hong Kong undergraduate student's lived experiences of second language (L2) investments and identities across different contexts, including inside and outside the classroom on the university campus, in the professional workplace, and during study abroad. Findings indicate that the student's differential L2 investments across contexts appear to be closely intertwined with the different identities constructed in specific circumstances and mediated by the perceived likelihood of yielding a good return on the investments. His selective L2 investments were also found to be driven by a desire for membership in an imagined international community and an imagined identity associated with a cosmopolitan lifestyle in the projected future. The article argues for the importance of a holistic understanding of individuals' L2 learning experiences both inside and outside the classroom in order to appreciate the complexities of their variable L2 investments and identities across contexts.